C-H functionalization of pyridines - Maity, Susmita; Bera, Asish; Bhattacharjya, Ayantika; Maity, Pradip (Organic & Biomolecular Chemistry, 2023)
Pyridine and its reduced form (piperidine) are the most common nitrogen heterocycles in FDA-approved drugs. Additionally, their presence in alkaloids, ligands for transition metals, catalysts, and organic materials with various properties makes them among the most important structural cores. Despite its importance, direct and selective functionalization of pyridine remains scarce due to its electron-poor nature and nitrogen coordination power. Instead, functionalized pyridine rings were primarily constructed from suitably substituted acyclic precursors. The focus on sustainable chemistry with minimum waste generation encourages chemists to develop direct C-H functionalization. This review summarizes different approaches to tackle the reactivity and regio- and stereoselectivity aspects for direct pyridine C-H functionalization.

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.